Towards Sustainable Energy Development: Integrating Traditional and Renewable Energy in Azerbaijan’s Energy Policy - R. A. Aliev (Vestnik MGIMO-Universiteta)
The article examines the formation of Azerbaijan's energy policy and the multivector development of its fuel and energy complex. In the context of global transformations and changes in energy flow structures, the author emphasizes the balanced development of both hydrocarbon and carbon-free segments of energy. The proposed concept of sustainable energy development envisages the harmonious coexistence of traditional and renewable energy, enhancing Azerbaijan's economic stability and geopolitical influence. The significant role of the oil and gas sector, demonstrated by successful projects and substantial foreign investments, is reinforced by the active development of renewable energy sources. Azerbaijan implements large-scale projects in wind and solar energy, as well as initiatives for the production of «green» hydrogen, which contributes not only to the reduction of emissions but also to the expansion of the country's export potential. The article highlights the importance of balanced FEC development, focusing on emission minimization through the application of carbon capture and utilization (CCUS) technologies, as well as the need for infrastructure modernization to improve energy efficiency. Azerbaijan demonstrates a unique case where traditional and renewable energy do not compete but complement each other, strengthening its positions in international cooperation and within the framework of the Greater Eurasian Partnership.